Empowerment of Financial Literacy in the Era of Digitalization 5.0 MSME Trade at the Bandung City Chamber of Commerce - Hertina, Dede; Hendayana, Yana; Ichsani, Sakina; Fatihat, Gita Genia; Pratiwi, Leni Nur (Unram Journal of Community Service, 2024)
Technological developments have brought us to an era where digital financial literacy has become very important, especially for people accustomed to the digital world. In today's digital era, skills in managing finances are no longer enough just to count money conventionally. The micro, small, and medium enterprises sector plays a vital role in the national economy, especially in creating jobs and increasing people's income. Based on this, the Community Service implementation team held training and outreach activities with the theme Empowering Financial Literacy in the Era of Digitalization 5.0 Micro, Small and Medium Enterprise Trade at the Bandung City Chamber of Commerce and Industry. Community Service Activities in the form of presenting material regarding Financial Literacy Empowerment in the Digitalization Era 5.0 will be held on July 31 2024. 15 Bandung City KADIN Micro, Small and Medium Enterprise partners who attended this activity have businesses in the culinary, fashion, service and trade sectors. The activities went well based on the evaluation results, and the training materials were based on work needs. A follow-up to this activity is the need for a sustainability program with the help of lecturers from the Faculty of Economics and Business, Widyatama University and KADIN Bandung City to help partners in the field of Financial Technology so that partners and the community can maximize training and development of financial literacy, especially for MSMEs in the Era-based trade sector. Digital 5.0 is vital because the micro, small, and medium enterprises sector is essential in advancing the country's economy.